DETECTION OF CAMPYLOBACTER SPP. WITH REAL-TIME POLYMERASE CHAIN REACTION - G. S. Skitovich; K. V. Serova; N. B. Shadrova; O. V. Pruntova (Ветеринария сегодня)
Bacteria of Campylobacter genus are ones of the main zoonotic pathogens causing human and animal diseases. Campylobacter organisms are microaerophiles and, therefore, require low oxygen concentration (3–5%) and high carbon dioxide concentration (3–10%) for their growth. They use amino acids rather than carbons as a source of energy. Classical bacteriological methods for Campylobacter spp. detection are not always successful due to diffi culties in creating optimal conditions for their growth. Therewith, development and implementation of molecular methods for Campylobacter detection and identifi cation are of current importance. Assay for qualitative Campylobacter spp. detection with real-time polymerase chain reaction using CFX-96 thermocycler was optimized. Highly specifi c segment of 16S rRNA gene allowing identifi cation of 6 Campylobacter species: C. jejuni, C. coli, C. lari, C. upsaliensis, C. helveticus и C. hyointestinalis was selected as an amplifi cation target. Optimal magnesium ion concentration (2.5 мМ) and primer annealing temperature (58 °С) were determined. Eighteen reference strains of various bacteria were tested. Only tests of Campylobacter genus strains gave positive results. The method sensitivity was 40 target molecules. The said method was used for testing 76 samples of raw materials of animal origin. Campylobacter spp. genome was detected in 18 samples. Obtained results showed that the optimized variant of real-time polymerase chain reaction based on 16S rRNA gene amplifi cation was a specifi c, sensitive, rapid, reproducible and accurate method for qualitative detection of Campylobacter spp. in samples of raw animal materials.